MANAJEMENT OF CHARACTER-BASED LEARNING (Multi Case Study at the Junior High School (SMP): Citra Berkat, Negeri I Pandaan, and Panti Parama Pasuruan, Indonesia) - P.G, Indriani,; Ulfatin, Nurul; Arifin, Imron; *, Kusmintardjo (IJRDO- Journal of Educational Research, 2017)
The purpose of this study is to describe the management of character-based defenders. This research was conducted through qualitative approach with muti-case design in three Junior High Schools. The data were collected by three techniques: wawanca-ra, observation, and documentation study. Researcher as a kun-ci instrument. Data analysis is done through two stages: case analysis, and cross-case analysis. The results show that character-based learning management varies in planning, organizing, mobilizing, evaluating and monitoring, as well as efforts to improve its quality.